Molecular Epidemiological Investigation of Canine Distemper Infection in Dogs and its Effect on Haemato-biochemical, Oxidative and CNS Biomarkers - Ralte, Malsawmtluangi; Sarma, Kalyan; Roychoudhury, Parimal; Konwar, Bedanga; Tolenkhomba, T. C.; Rajesh, J. B.; Behera, S. K.; Thakur, Neeraj; Das, Agniranjan (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted (July, 2022–June, 2025) in and around the Aizawl district of Mizoram to know the epidemiological status of canine distemper infection in dogs in the Aizawl district of Mizoram and its effect on haemato-biochemical, oxidative and CNS biomarkers. Canine distemper virus (CDV) infection was responsible for high morbidity and mortality in dogs worldwide. A limited number of studies have been carried out on canine distemper in Mizoram. Out of 1000, 95 cases (9.5%) were confirmed positive by a rapid diagnostic kit and molecular technique with a high case fatality rate (86.32%). CDV remains a serious threat to canine health, particularly in non-vaccinated, purebred, and young (1–2 years) dogs, with winter showing peak incidence in Mizoram. PCR amplification of positive cDNA yielded a 286 bp fragment of the partial nucleocapsid (N) gene of CDV which was identical to each other and showed 96.2–100% identity within the Asia-1 genotype of CDV, indicating low polymorphism. It may be responsible for hematobiochemical alterations, oxidative stress imbalance, changes in CNS-specific biomarkers, and cerebrospinal fluid abnormalities. The progressive elevation of myelin basic protein (MBP) and Neuron-specific enolase (NSE) in non-survivors indicates severe demyelination and neuronal damage in advanced CDV infection. Overall, integration of hemato-biochemical, oxidative, CNS biomarkers and CSF, data provides a comprehensive approach for assessing disease severity, predicting outcomes, and differentiating survivors from non-survivors.